Efficient heterologous expression of cytochrome P450 enzymes in microorganisms for the biosynthesis of natural products. (17th February 2023) - Hu, Baodong; Zhao, Xinrui; Wang, Endao; Zhou, Jingwen; Li, Jianghua; Chen, Jian; Du, Guocheng
Abstract: Natural products, a chemically and structurally diverse class of molecules, possess a wide spectrum of biological activities, have been used therapeutically for millennia, and have provided many lead compounds for the development of synthetic drugs. Cytochrome P450 enzymes (P450s, CYP) are widespread in nature and are involved in the biosynthesis of many natural products. P450s are heme-containing enzymes that use molecular oxygen and the hydride donor NAD(P)H (coupled via enzymic redox partners) to catalyze the insertion of oxygen into C-H bonds in a regio- and stereo-selective manner, effecting hydroxylation and several other reactions. With the rapid development of systems biology, numerous novel P450s have been identified for the biosynthesis of natural products, but there are still several challenges to the efficient heterologous expression of active P450s. This review covers recent developments in P450 research and development, including the properties and functions of P450s, discovery and mining of novel P450s, modification and screening of P450 mutants, improved heterologous expression of P450s in microbial hosts, efficient whole-cell transformation with P450s, and current applications of P450s for the biosynthesis of natural products. This resource provides a solid foundation for the application of highly active and stable P450s in microbial cell factories to biosynthesize natural products.